Determination of the comfort zone for intergingival height and its practical application to treatment planning: A survey - Shefali Pareek; M S Rani (Wolters Kluwer Medknow Publications, 2012)
Background: The concept of the 'comfort zone' for intergingival height is a simple guideline to help establish the correct vertical dimension necessary for occlusal harmony in any individual. It can be used as a guide for identifying individuals at relatively greater risk of developing temporomandibular dysfunction and also when rebuilding the occlusion in the treatment of patients with temporomandibular dysfunction. The intergingival height varies according to the patient's age and stage of development, as well as with the height of the incisor crowns. In orthodontics this parameter can be used to track the progress of a patient being treated with functional appliances. This parameter has not been studied in detail and hence this survey was designed and conducted to gain information regarding its significance. Objectives: The objectives of this survey were to estimate the value of 'comfort zone' for intergingival height in the region of the central incisor and to establish the norm for the comfort zone in males and females. Materials and Methods: The intergingival height was measured in the region of the right central incisor using a vernier caliper. The intergingival height was measured as the vertical distance from the midpoint of the free gingival margin of the right maxillary central incisor to a similar point on the right mandibular central incisor, with the teeth in occlusion. Results: According to the results of this, the range for the comfort zone for intergingival height in all subjects was 15.96-16.55 mm. The range for female subjects was 14.86-15.32 mm and the range for male subjects was 17.12-17.67 mm. Conclusion: The comfort zone of intergingival height should become a part of our vocabulary and should be routinely utilized as a guideline for consistently achieving the correct vertical dimension at the end of treatment. The areas of utilization of this measurement are many and it should be used to assist in achieving better and more stable clinical results.